2022
DOI: 10.3389/fendo.2022.1004962
|View full text |Cite
|
Sign up to set email alerts
|

Application and prospect of trabecular bone score in differentiated thyroid cancer patients receiving thyrotropin suppression therapy

Abstract: Thyroid-stimulating hormone (TSH) suppression therapy is one of the common treatments for most patients with differentiated thyroid cancer (DTC). Unfortunately, its detrimental effects on bone health are receiving increasing attention. It may increase the risk of osteoporosis and osteoporotic fractures. The trabecular bone score (TBS) is a relatively new gray-scale texture measurement parameter that reflects bone microarchitecture and bone strength and has been shown to independently predict fracture risk. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 104 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…Comparing with BMD, TBS provides a more comprehensive re ection of bone data and is particularly useful in assessing fracture risk in individuals with normal bone density but compromised bone microstructure [6]. Studies have demonstrated that TBS exhibits superior fracture risk prediction capabilities compared to BMD, particularly in individuals with risk factors such as rheumatoid arthritis, primary hyperparathyroidism, and thyroid cancer patients undergoing suppressive therapy with thyroid-stimulating hormone [14][15][16]. TBS is recognized as an independent risk factor for fractures and has been consistently shown to predict both current and future fragility fractures, regardless of BMD and FRAX assessments [5,6,17].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with BMD, TBS provides a more comprehensive re ection of bone data and is particularly useful in assessing fracture risk in individuals with normal bone density but compromised bone microstructure [6]. Studies have demonstrated that TBS exhibits superior fracture risk prediction capabilities compared to BMD, particularly in individuals with risk factors such as rheumatoid arthritis, primary hyperparathyroidism, and thyroid cancer patients undergoing suppressive therapy with thyroid-stimulating hormone [14][15][16]. TBS is recognized as an independent risk factor for fractures and has been consistently shown to predict both current and future fragility fractures, regardless of BMD and FRAX assessments [5,6,17].…”
Section: Discussionmentioning
confidence: 99%